Characterization of FCC slurry oil products thermally converted over modified coke powder. (15th December 2022) - Li, Jiazhou; Chen, Xiaodong; Zhang, Yuming; Xu, Jinghui; Liu, Yindong; Wang, Luhai; Zhang, Wei; Guo, Jinjun; Zhang, Wenbin; Sun, Qiang; Qi, Yunfei
Abstract: Slurry oil contains considerable amounts of aromatics but has the drawbacks of difficult cracking and easy coking. Fluidized thermal conversion technique realizes not only the aromatics enrichment but also the removal of solid particles in slurry oil. Herein, the fluidized thermal conversion of slurry oil using unmodified Coke, Ni-modified Coke and Fe-modified Coke as heat carriers were investigated at 500 °C by a fluidized bed reactor. The results demonstrated that two modified Coke produced the lower oil yields of 83.33 wt% (Ni-modified Coke) and 82.57 wt% (Fe-modified Coke) and the higher coke yields of 14.72 wt% (Ni-modified Coke) and 15.59 wt% (Fe-modified Coke) in comparison to the oil and coke yields of 84.02 and 14.21 wt% over unmodified Coke. Moreover, the yield of gas product H2 increased significantly from 5.0 mL/g (unmodified Coke) to 17.5 mL/g (Fe-modified Coke) and 22.4 mL/g (Ni-modified Coke). Slurry oil consisted mainly of aromatics, of which aromatics with two to five rings accounted for 77.14 wt%. Upon using unmodified Coke, Ni-modified Coke and Fe-modified Coke, the proportion of aromatics with two to five rings increased up to 85.86, 89.49 and 87.08 wt% respectively, realizing the aromatics enrichment effectively. Fluidized thermal conversion also facilitated the solid particles removal from slurry oil. The removal rates over unmodified Coke, Ni-modified Coke and Fe-modified Coke were higher than 95%. All above experimental results indicated that fluidized thermal conversion technique could realize the efficient utilization of both slurry oil and fluidized coke powder. The aromatics enrichment and the solid particles removal in slurry oil could be achieved efficiently. Highlights: Fluidized thermal conversion of slurry oil was conducted. Performances of coke powder and modified coke powder as heat carriers were determined. Aromatic hydrocarbon enrichment of slurry oil was achieved. Solid particle removal from slurry oil was performed.